Mechanical performance and carbonation resistance of basalt fiber—polypropylene fiber rubber concrete - Kun, Liu; Xin, Liu Hua; Bei, Liu Bei; Nan, Liu Ya (Frontiers in Materials, 2023)
In this study, 5%, 10%, and 15% rubber particles were used to replace fine sand in concrete, and basalt fibers (0.1%, 0.2%, and 0.3%) and polypropylene fibers (0.1%, 0.15%, and 0.2%) were added to rubber concrete to prepare hybrid fiber rubber concrete (HFRC). The experiments investigated the changes of mechanical properties of basalt (BF), polypropylene (PPF) fibers, and rubber particles when they were blended into concrete respectively, and the degree of influence of each factor on the mechanical and carbonation resistance of HFRC was investigated based on the orthogonal test. The results show that the rubber concrete's mechanical and carbonation properties are improved to varying degrees after adding hybrid fibers. When the basalt fiber content is 0.2% and the polypropylene fiber content is 0.15%, the overall mechanical properties of HFRC reach the best state. When the basalt fiber content is 0.2%, the polypropylene fiber content is 0.15%, and the rubber content is 5%, the carbonation resistance of HFRC is the most ideal. In addition, the microstructure of HFRC was observed by scanning electron microscope.